Importance of achieving the financial equilibrium in the economic corporation Analytical study of a sample of petroleum group for the period (2019/2020) - amirouche, Boubekeur (Journal of Research in Finance and Accounting, 2022)
This article aims to evaluate the financial equilibrium of three petroleum group for 2019 & 2020, We concluded that the financial equilibrium of Total and Sonatrach is good because they achieved all the conditions in the two years and obtained a positive treasury scenario, But Total is the best because it achieved a higher rate of net treasury in 2020 than Sonatrach. While ExxonMobil group suffers from financial Disequilibrium because it did not achieve any condition and was crowned with an abnormal and dangerous scenario, but it began to recover in 2020.